2002
DOI: 10.1063/1.1425073
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics and thermal stability of n+ polycrystalline- Si/ZrO2/SiO2/Si metal–oxide–semiconductor capacitors

Abstract: We have investigated the thermal stability of n+ polycrystalline-Si(poly-Si)/ZrO2(50–140 Å)/SiO2(7 Å)/p-Si metal–oxide–semiconductor (MOS) capacitors via electrical and material characterization. The ZrO2 gate dielectric was prepared by atomic layer chemical vapor deposition using ZrCl4 and H2O vapor. Capacitance–voltage hysteresis as small as ∼12 mV with the flatband voltage of −0.5 V and the interface trap density of ∼5×1010 cm−2 eV−1 were attained with activation anneal at 750 °C. A high level of gate leaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…It is in- teresting to observe that the effective fixed charge density, (Q SiO x /Si ϩQ ZrO 2 /SiO x ), in the stacked dielectric changes from negative to positive when increasing the film thickness of ZrO 2 above 6.0 nm. A similar sign change of fixed charge was also observed by Houssa et al 15 and Lim et al 33 in the postdeposition oxidation anneal of ZrO 2 /SiO x stacked dielectrics. Houssa et al suggested that the change of fixed charge from negative to positive was caused by the generation of hydrogen-induced overcoordinated oxygen centers by oxidation at high temperature.…”
Section: Resultssupporting
confidence: 70%
“…It is in- teresting to observe that the effective fixed charge density, (Q SiO x /Si ϩQ ZrO 2 /SiO x ), in the stacked dielectric changes from negative to positive when increasing the film thickness of ZrO 2 above 6.0 nm. A similar sign change of fixed charge was also observed by Houssa et al 15 and Lim et al 33 in the postdeposition oxidation anneal of ZrO 2 /SiO x stacked dielectrics. Houssa et al suggested that the change of fixed charge from negative to positive was caused by the generation of hydrogen-induced overcoordinated oxygen centers by oxidation at high temperature.…”
Section: Resultssupporting
confidence: 70%
“…Given the weak temperature dependence it is suggested that some kind of tunnelling operates in this case. It is found that the curve is well fitted by a field-assisted tunnelling which is represented by the equation [41,42] J ∝ E 2 t exp − 8π 3h…”
Section: Leakage Current Characteristics and Conduction Mechanismsmentioning
confidence: 94%
“…10 Several studies have already reported the effect of postdeposition annealing (PDA) on the insulating properties of HfO 2 and ZrO 2 . 11,12 It has been reported that the PDA generally degrades the dielectric performance (decrease the capacitance density and increase the leakage current) of these films. However, a comparative study of two films deposited by atomic layer deposition (ALD) using similar precursors and process conditions has not been systematically reported.…”
mentioning
confidence: 99%